DEVELOPMENT POLE AND GROWTH POINTS OF INNOVATIVE ECONOMY: KAZAKHSTAN AND FOREIGN EXPERIENCE - Mugayeva Raikhan Uljagalievna; Uchkampirova Aigul Bahadirovna (Academic Journal of Physical and Chemical Sciences, 2020)
The article discusses the innovative development of the poles, as well as monitoring a comprehensive assessment of the innovative activities of the regions. This study indicates that increased innovation activity provides economic growth. "Growth points", which should be understood as a company, "the effect of enthusiasm, form the "development zone" in the region or country. From single-valued and high-time to the basics of unpolished theory, the theory of polar poles (PRT) is derived. By the middle of the great part, in regional economy the theory of the polar poles – this concept, the theoretic object of the duality of the divergence of the differentiation of the duality of the duality of the duality in the market of products In keeping with this concept, the mid-region is characterized by the propagating (dynamically divisive, diverging) propulsion. It stimulates the dilatation of the dilapidated territory, in the opposite direction, in accordance with the instructions of the addictive, addictive and obsessive persons, presiding over the polar pole of the border, with a higher concentration in the subordinate area of the recital zone. Rather central mogwt how razvïvatsya stïxïyno, so, and celenapravlenno way optïmalnogo razmeşçenïya sootvetstvwyuşçïx Enterprise and blagoprïyatnıx create wslovïy Their xozyaystvennoy Activities pomoşçyu razlïçnıx ïstoçnïkov fïnansïrovanïya (of State vlojenïy, çastnogo capital, subsidies, nalogovıx lax and others.). Once you have developed in the region, you will have a far more complex development of the whole process, as you would expect, under the mechanisms of market economy.